Polymorphic CAG and GGN repeats in Cryptorchidism patient risk: A meta-analytical study - Nurul Cholifah Lutfiana; Athaya Febriantyo Purnomo; Nur Aisah Ibrahimiyah (Universitas Muhammadiyah Surabaya, 2024)
Genetic mutations in the androgen receptor (AR) gene have been identified as the cause of androgen insensitivity syndrome. These mutations are linked to inconsistent development of the Wolffian duct and may result in conditions such as micropenis, hypospadias, and cryptorchidism. The androgen receptor has two polymorphic sites located in exon 1, which consists of varying amounts of CAG and GGN repeats. These repetitions lead to the formation of polyglutamine and polyglycine stretches of varied lengths. Increased CAG repeats lead to a decrease in androgen receptor transcriptional activity, but the impact of GGN triplets is less well understood. This research examined the CAG and GGN repeat lengths in males who had a past medical record of cryptorchidism. Prospective and retrospective observational studies from PubMed, Science Direct, and Embase were systematically searched up to 15th November 2020. Primary outcomes were analyzed using a fixed or random effect model regarding its heterogeneity and continued with multilevel modeling of each polymorphism and ethnicity. CAG and GGN repeat polymorphism was found to be significantly different compared to control in contributing to cryptorchidism (CAG: 0.55 [CI 95%=0.19-0.91]; p-value=0.003 and GGN 0.90 [CI95%=0.65-1.15]; p value<0.000). In conclusion, CAG and GGN repeat polymorphism have an essential role in the incidence of cryptorchidism.